Statistical optimization of simultaneous saccharification fermentative hydrogen production from corn stover. Issue 1 (1st January 2020) - Jing, Yanyan; Li, Fang; Li, Yameng; Jin, Peng; Zhu, Shengnan; He, Chao; Zhao, Junhui; Zhang, Zhiping; Zhang, Quanguo
ABSTRACT: Corn stovers are rich in carbohydrates and can be used by anaerobic bacteria to produce hydrogen by fermentation. In the present study, using hydrogen production as the main experimental index, the effect of different influential factors on hydrogen production from corn stover saccharification and fermentation was studied, using the response surface method BBD model. The significance of interactions between different influential factors on hydrogen production by simultaneous saccharification and fermentation of corn stover material were investigated and optimized. Results showed that there were several factors affecting simultaneous saccharification fermentative hydrogen production from corn stover, including substrate concentration, inoculation amount, pH value and enzyme concentration. In linear terms, substrate concentration had the greatest influence on hydrogen production by anaerobic simultaneous saccharification and fermentation. In terms of multi-factor interactions, the interaction between pH and enzyme concentration was the most significant. The optimal hydrogen production conditions established from the BBD model were as follows: substrate concentration of 25 mg/mL, inoculation amount proportion of 32.62%, initial pH value of 6.50 and enzyme concentration of 172.08 mg/g, resulting in the maximum hydrogen production of 55.29 mL/g TS. The actual maximum hydrogen production reached 56.66 mL/g TS, with these experimental results consistent with the predicted value established from equation fitting. This study provides a reference for hydrogen production by anaerobic synchronous saccharification fermentation using corn stover as substrate and lays a foundation and provides technical support for the industrialization of biological hydrogen production using corn stover as substrate. Graphical abstract: